AN ANALYSIS OF STUDENTS’ DIFFICULTIES IN READING COMPREHENSION THROUGH ONLINE LEARNING - RACHMANITA, RACHMANITA; SAPTARINA, EVA; AMELIA, TIARA (Linguists : Journal of Linguistics and Language Teaching, 2022)
A primary objective of the study was to explore students' difficulties in reading comprehension through online learning using Google Classroom and Zoom meetings faced by eighth-grade students at SMP Persatuan Pedamaran OKI regency. This study used a descriptive qualitative method; the participants were all eighth-grade students at SMP Persatuan Pedamaran. The data was gathered using a reading comprehension test and questionnaires. The test indicated that 77.5 percent of students struggled with the text's main idea. Then, 72.78 percent of students had a problem with the text's generic structure, and 75.83 percent had difficulty with references. Next, 73.75 percent of students had problems with the moral value of the text. Following that, 72.25 percent of students had difficulties understanding the text's details. Finally, 73.25 percent of students needed help finding the meaning of vocabulary in the text. Further, based on the questionnaires, it was found that the problems in learning reading comprehension online focused on several factors: students' background, social situation, school scene, and teacher's teaching strategy. In conclusion, many students in SMP Persatuan Pedamaran found it hard to read the texts comprehensively, especially in online learning.